Intracellular Lipid Accumulation and Mitochondrial Dysfunction Accompanies Endoplasmic Reticulum Stress Caused by Loss of the Co-chaperone DNAJC3 - Jennings, Matthew J.; Hathazi, Denisa; Nguyen, Chi D. L.; Munro, Benjamin; Münchberg, Ute; Ahrends, Robert; Schenck, Annette; Eidhof, Ilse; Freier, Erik; Synofzik, Matthis; Horvath, Rita; Roos, Andreas (Frontiers in Cell and Developmental Biology, 2021)
Recessive mutations in DNAJC3, an endoplasmic reticulum (ER)-resident BiP co-chaperone, have been identified in patients with multisystemic neurodegeneration and diabetes mellitus. To further unravel these pathomechanisms we employed a non-biased proteomic approach and identified dysregulation of several key cellular pathways, suggesting a pathophysiological interplay of perturbed lipid metabolism, mitochondrial bioenergetics, ER-Golgi function, and amyloid-beta processing. Further functional investigations in fibroblasts of patients with DNAJC3 mutations detected cellular accumulation of lipids, and an increased sensitivity to cholesterol-stress, which led to activation of the unfolded protein response (UPR), alterations of the ER-Golgi machinery, a defect of APP. In line with the results of previous studies, we describe here alterations in mitochondrial morphology and function, as a major contributor to the DNAJC3 pathophysiology. Hence, we propose that the loss of DNAJC3 affects lipid/cholesterol homeostasis, leading to UPR activation, Aβ accumulation and impairment of mitochondrial oxidative phosphorylation.